Strategies Used By Lecturers In Teaching Writing - Roza Susanti; Dwi Settya Mahaputri (Jurnal Ilmiah Al-Furqan: Al-qur'an Bahasa dan Seni, 2022)
Strategies in writing that usually used by lecturers are STOP, AIM, PLAN, KWL, plot diagram, WRITE, DARE, CDO, color coding, COPS, job card, sumarization, collaborative writing, word processing, inquiry activities, TTW and pictures. The purpose of this reseach was to know the strategy used by lecturers in teaching writing at STKIP Yayasan Abdi Pendidikan. The research participants were English Department lecturers who teach writing. In collecting the data, the researcher used interview. In choosing the participants, the researcher used purposive sampling. The researrhcer used peer-debriefing in checking data trustworthiness that got by the researcher. In data analysis, the researcher did Data managing, Reading or Memoing, Classifying, Interpreting, Writing Report. After analyzing, the resercher found that strategies used by lecturers in teaching writing were STOP, AIM, PLAN, Plot diagram, WRITE, CDO, COPS, SRSD, Smmarization, inquiry activities. Stratgies that seldom used by lecturers in teaching writing were KWL, job cards, CW, Word processing, pictures dan TTW. Then, strategies that never used by lecturers were color codding strategy.